Sistem Pakar Kasus dan Aturan pada Hukum Kesehatan Indonesia Berbasis Android - Admi Syarif; Noverina Rahmaniyanti; Yulia K. Wardani; Kurnia Muludi (Lambung Mangkurat University, 2023)
The doctor-patient relationship is not always harmonious. Not only that, but patients also often have problems with other health workers such as midwives, nurses, and others. Health disputes are caused by patient disappointment and dissatisfaction with the services and medical treatment received before, during, or after treatment This study aims to build an expert system for identifying health dispute cases and related rules Android-based. This system adopts an Android-based forward chaining method. The system is tested using 5 actors and 35 cases. The results obtained are compared with the results given by the experts. The test results show that the system is effective in explaining the rules based on the case.